Post IPO dynamics of capital structure on the Johannesburg Stock Exchange - C. Chipeta (South African Journal of Business Management, 2016)
This paper examines the dynamics of capital structure for firms engaging in initial public offerings (IPOs) on the Johannesburg Stock Exchange (JSE). Censored Tobit regressions are used to model capital structure targeting behaviour. The findings suggest evidence of targeting behaviour consistent with the static trade off theory of capital structure. On average, IPO firms adjust towards the capital structure target at a faster pace than seasoned firms; IPO firms take, on average, 0.77 years to cover half the financing gap, whereas seasoned firms take an average of 2.65 years. In the first year following the IPO, hot market IPOs significantly reduce their total debt, while cold market IPOs increase the total debt significantly. In terms of the total debt ratio, hot market IPOs adjust at a marginally faster pace than cold market IPOs. However, the opposite is true when the long term debt ratio is considered. In addition, hot market IPOs adjust faster than cold market IPOs in the first year following the IPO. The average first year adjustment speed of hot market IPO firms is 45.61 percent higher than the speed of adjustment for the average cold market IPO firm.
Keywords: 650